Estradiol: micrograms or milligrams. (1st February 2016) - Kirk, Jeremy M W; Wickramasuriya, Nalin; Shaw, Nicholas J
Summary: Estrogen is used to induce puberty in peripubertal girls with hypogonadism. Although both synthetic and natural forms are available, along with different routes of administration, in the UK oral ethinyl estradiol and the low-dose oral contraceptive pill are commonly used as hormone replacement therapy for practical reasons. We present five peripubertal girls (aged 12.5–14.9 years) with hypogonadism (two with primary hypogonadism due to Turner syndrome and three with central (secondary) hypogonadism as part of multiple pituitary hormone deficiency) who for a variety of reasons have received milligram doses of estradiol (E2 ) in error for between 6 weeks and 6 months, instead of the expected microgram doses of ethinyl estradiol. Although there are no direct comparisons in peripubertal girls between synthetic and natural estrogens, all girls had vaginal bleeding whilst receiving the milligram doses and have ended up with reduced final heights, below the 9th centile in 1 and below the 2nd centile in 4. Whilst reduction in final height may be part of the underlying condition (especially in Turner syndrome) the two girls with height predictions performed prior to receiving the estrogen overdose have not achieved their predicted height. Estrogen is one of the few drugs which is available in both milligram and microgram formulations. Clinicians need to be alert to the possibility of patients receiving the wrong formulation and dosage in error. Learning points: Girls with primary and secondary gonadal failure require assistance with pubertal induction. Although several different formulations and route of administration are available, for practical reasons, the majority of girls in the UK receive oral ethinyl estradiol. Estrogen preparations are available in both milligram and microgram formulations, with potential for receiving the wrong dose. Girls receiving milligram rather than microgram preparations all had vaginal bleeding and a short final height.